'Epistemic Injustice' and the 'Right Not to Be Poor': Bringing Recognition into the Debate on Global Justice. Issue 4 (November 2013) - Gentile, Valentina
Abstract : Poverty and inequality are not the sole sources of (global) injustices. And the latter are not only a matter of fair distribution. Identity and cultural asymmetries, often articulated along political and economic lines, relocate and reshape the struggle against subordination to include new areas of contestation, such as gender, race, ethnicity, sexuality, culture, religion and nationality.